3,4-dihydroxybenzaldehyde 4-phenyl-thiosemicarbazone - Tan, Kong Wai; Ng, S.W.; Maah, Mohd Jamil; Ng, C.H.; Farina, Y. (International Union of Crystallography, 2008)
Molecules of the title compound, C14H13N3O2S, are linked by intermolecular O-H center dot center dot center dot O hydrogen bonds into centrosymmetric dimers forming R-2(2)(4) rings which are further linked by O-H center dot center dot center dot S hydrogen bonds and weaker N-H center dot center dot center dot S and N-H center dot center dot center dot O hydrogen bonds to form a three-dimensional network.